Challenges of conducting distance learning during Covid-19 pandemic: the case of Google classroom and WhatsApp - Vigo Dewangga; Pramudana Ihsan; Abdulsuko Dina (PROCEEDING UMSURABAYA, 2020)
Abstract. Corona virus outbreak have shocked the world. All human activities have ground to a halt because of the covid 19 pandemic. Many sectors is going down. Schools closed, workplaces shut down, multiple religious services cancelled and places of worship are closed. A number of schools around the world closed, including Indonesia. Teaching learning process should be continued eventhough many schools shut down. Indonesian government, ministry of education and culture, decide to shut schools and keep students study at home in order to break the chain of spreading corona virus. They are partnering with Television of the Republic of Indonesia (TVRI) to deliver educational content during dedicated hours. In addition, many schools are implementing study from home (SFH). They try to connect the students and the teachers through online platforms. Under theseunexpected conditions, the teachers have had to quickly adapt to mingle up in thiscircumstances to make sure that the learning goals achieved and the students engage in learning. This paper focuses on the social media based online learning platform, namely Google classroom and WhatsApp. The aim of this study is to find out the students perception towards the use of Google classroom and WhatsApp in learning English. The study was conducted in a descriptive research. The result of this study revealed that Clinical Nutrition department students at Politeknik Negeri Jember come to realize Google classroom as a social media based online learning platform that is easy to use, interesting and enjoyable than using WhatsApp for learning English.